The Role of Hippocampal Functional Connectivity on Multisystem Subclinical Abnormalities in Schizophrenia. Issue 6 (July 2020) - Hare, Stephanie M.; Chiappelli, Joshua; Savransky, Anya; Adhikari, Bhim M.; Wisner, Krista; Kvarta, Mark; Goldwaser, Eric; Du, Xiaoming; Chen, Shuo; Rowland, Laura M.; Kochunov, Peter; Hong, L. Elliot
ABSTRACT: Objective: Schizophrenia is associated with excess medical mortality: patients have an average life expectancy one to two decades shorter than the general population. This study investigates the relationship between aberrant hippocampal resting-state functional connectivity in schizophrenia and cumulative subclinical effects of chronic stress on metabolic, cardiovascular, and immune function using the allostatic load index. Methods: Cumulative stress was estimated using allostatic load total score (range, 0–13) in 46 patients with schizophrenia and 31 controls matched for age and sex (patients: age = 36.1 [13.7] years, sex = 32/14 male/female; controls: age = 35.5 [14.1], sex = 21/10 male/female). Hippocampal functional connectivity was assessed using resting-state functional magnetic resonance imaging; hippocampal structural connectivity was assessed using fornix fractional anisotropy. Linear regression analysis was used a) to test the hypothesis that aberrant hippocampal resting-state functional connectivity in schizophrenia (identified in analysis of schizophrenia − control differences) is associated with elevated allostatic load scores in patients and b) to determine the association between fornix fractional anisotropy with allostatic load. Results: In patients, higher allostatic load was significantly associated with reduced resting functional connectivity between the left hippocampus and right cingulate cortex and left precentral gyrus, but higher connectivity between the right hippocampus and left cerebellum lobe VI (corrected p values <. 05). In controls, reductions in both hippocampal structural connectivity and hippocampal-cingulate functional connectivity were associated with higher allostatic load scores. Conclusions: These findings support basic neuroscience evidence that cumulative stress and hippocampal function are closely connected and suggest that abnormal hippocampal functional communication in schizophrenia may be related to elevated multisystem subclinical medical issues in patients as indexed by allostatic load. Abstract : Supplemental digital content is available in the text.